Bilateral ovarian metastases as the presenting manifestation of lung carcinoid in a 50-year-old woman: Case study and review of literature - Subhashis Mitra; Amiya Jhunjhunwala; Hema Chakraborty (Wolters Kluwer Medknow Publications, 2017)
Neuroendocrine tumors (NETs) are neoplasms arising from dispersed neuroendocrine cells, localized to the gastrointestinal tract (GIT), lungs, adrenal medulla, and other sites. The term "carcinoid tumor" is usually limited to NETs of the lung and GIT. Ovarian carcinoids are uncommon, accounting for 0.1% of ovarian malignancies and 5% of all NETs. Primary ovarian tumors arise in pure form or as a component of teratomas, while ovarian NET metastases are predominantly from gastrointestinal primaries. To the best of our knowledge, there are only two previous reports of bronchopulmonary carcinoids (PCs) metastasizing to the ovaries. We describe a case of PC in a 50-year-old woman, with bilateral ovarian tumors as the presenting manifestation of the disease, and discuss the clinical and pathobiologic significance of this presentation.